2021
DOI: 10.1109/ojap.2021.3067435
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Tailoring the Gain Pattern of a Single Antenna Element

Abstract: In this paper, we present a novel method to tailor the radiation pattern of an antenna element, such as a single element of an array, by maximing its partial radiation efficiency in the desired angular space. The tailored pattern of the single element is achieved by current distribution synthesis using multiple feed points in the antenna. A method to determine and realize the currents at the feeds is presented. The method is demonstrated by designing and manufacturing a four-element linear array consisting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…The proposed method is a major extension to the earlier works, where a multi-port antenna has been optimized in terms of port currents while maximizing the radiation efficiency [17], or the partial radiation efficiency in a certain angular range [18]. The earlier work [18] has covered optimization of single multi-port antennas and an array separately, whereas in this paper, we aim to optimize both antenna array and its multi-port antenna elements simultaneously. We create a model for determining the realized gain at different angles as a function of element-level port impedances and signals, and array-level weights.…”
Section: Theory Of the Model And Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed method is a major extension to the earlier works, where a multi-port antenna has been optimized in terms of port currents while maximizing the radiation efficiency [17], or the partial radiation efficiency in a certain angular range [18]. The earlier work [18] has covered optimization of single multi-port antennas and an array separately, whereas in this paper, we aim to optimize both antenna array and its multi-port antenna elements simultaneously. We create a model for determining the realized gain at different angles as a function of element-level port impedances and signals, and array-level weights.…”
Section: Theory Of the Model And Methodsmentioning
confidence: 99%
“…where H denotes the Hermitian transpose, and a is a column vector of length M containing the port signals a m . Following [18], vector a is defined as…”
Section: B Model For Realized Gain In the General Casementioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has shown that the FoV can be successfully limited by constructing the array elements from fixed sub-arrays [3]- [7]. The sub-array approach can be further improved by synthesizing matching circuits for the individual sub-array elements [8]. However, the viability of sub-array techniques depends on the availability of sufficient space for sub-array feeding networks.…”
Section: Introductionmentioning
confidence: 99%